The mobile Patient Information Assistant (PIA) app during the inpatient surgical hospital stay: evaluation of usability and patient approval - Görtz, Magdalena; Wendeborn, Antonia; Müller, Michael; Hohenfellner, Markus (Healthcare, 2023)
Mobile eHealth apps are becoming increasingly important tools in healthcare management, capable of providing education and support at any time. There is little knowledge about surgical patients’ appreciation and use of these apps. The objective of this study was to develop and evaluate a user-friendly medical app (PIA; Patient Information Assistant) for providing individual patient information before and after inpatient urological surgery. ...
Gesehen am 21.11.2023